Performance Management in Improving Competitive Advantage at School - Rio Estetika; Imron Rosyadi; Muh. Nur Rochim Maksum (At-Ta'dib, 2022)
The problem of performance management in Islamic educational institutions is still often carried out for only periodic formal assessments for promotion/position. The fantastic number of Muhammadiyah educational institutions, in fact, does not necessarily show their competitive advantage as a whole. Muhammadiyah schools in the outskirts of Wonogiri district (rural areas) are often judged for their management from the road, labeled as discarded schools, unable to compete with public schools, and being underestimated by the community. Muhammadiyah educational institutions are expected to be able to get out of this situation by building a competitive advantage that can be achieved through proper performance management, in line with opportunities and the surrounding environment. Research at SD Muhammadiyah (PK) Pracimantoro and SD Muhammadiyah Inovatif Baturetno, aims to obtain a description based on field facts about planning, implementing, and evaluating performance management in achieving competitive advantage. This field research uses a qualitative approach by emphasizing the analysis of descriptive data in the form of written and spoken words and pictures. The data in this study were collected through interviews and documentation methods. Data analysis was carried out using the inductive method through several steps, namely: data collection accompanied by data reduction, presenting data in the form of narratives and descriptions, then drawing conclusions. The results of this study are performance management in achieving competitive advantage at SD Muhammadiyah PK Pracimantoro and SD Muhammadiyah Innovative Baturetno, carried out in three stages. First, planning includes: goal setting, recruitment of teachers and education personnel, performance agreements. Second, implementation. At the implementation stage of performance management contains several activities, namely: coaching discipline, motivation, competency development, and awards. Third, performance evaluationtaken by two approaches, namely formal and informal. This process is carried out in order to realize school excellence that focuses on educational aspects, including: (1) Location; (2) Value excellence, which includes: curriculum, educational services, teaching staff, infrastructure, educational programs, and graduate achievements.